PENYELESAIAN SENGKETA KEPEMILIKAN TANAH - Ayu Kemalasari, Ana Silviana*) , Yunanto (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2013)
In essence, the case of land is a conflict of interest (conflict of interest) in the land sector. In issuing a certificate to a process involving the applicant. Both oral and written explanation of the relevant parties have opportunities for fraud. As an example the case in the Land Office of the parcel of Semarang District 329 Sub Bambankerep Ngaliyan Semarang, Central Java Province. Based on these descriptions, the researchers interested in conducting research entitled: